Coping style, anxiety level, organizational support, and work commitment of educators during the COVID-19 pandemic in the Philippines: A mixed-methods study - Norhidayah A. Aragasi (Belitung Raya Foundation, 2021)
Background: The emergence of the COVID-19 pandemic has distorted the education system, which greatly challenged educators in the pursuit of the continuity and quality of education. Commitment to perform duties and responsibilities are bounded in coping with the situation, emotional state, and the support from the organization.